Merasa Asing dan Salah Tempat: Fenomena Uncanny dalam Novel Rubber Karya Madelon Syekely Lulofs - Sudibyo (Arif: Jurnal Sastra dan Kearifan Lokal, 2023)
Life on plantations in the first half of the 20th century, which was autonomous, gave a great freedom to the planters. They worked on the plantations almost without any interferences from the colonial government in Batavia. Everything related to the plantation companies was the initiative and policy of the planters themselves. However, the difference between reality and what they dreamed of before when they were still in the Netherlands eventually led to various uncanny phenomena such as feeling alienated, odd, and displaced. This paper aimed to reveal these various phenomena in Rubber's novel by using Homi K. Bhabha's postcolonialism theory which drew inspiration from Freud's psychoanalytic theory of unheimlich. The method used was the close reading method with the poststructuralism assumption that the text did not convey what appeared to be said at first, what will be said, or what is expected to be said. For this reason, reading was carried out carefully and repeatedly on lingual units in the form of text or fragments in Rubber in order that every sign, ideas and statements had meanings.